Survival of Neural Stem Cell Grafts in the Lesioned Spinal Cord Is Enhanced by a Combination of Treadmill Locomotor Training via Insulin-Like Growth Factor-1 Signaling - D. H. Hwang; H. Y. Shin; Minjeong Kwon; Jun Young Choi; Buom‐Yong Ryu; Byung Gon Kim (2014)
Combining cell transplantation with activity-based rehabilitation is a promising therapeutic approach for spinal cord repair. The present study was designed to investigate potential interactions between the transplantation (TP) of neural stem cells (NSCs) obtained at embryonic day 14 and treadmill training (TMT) in promoting locomotor recovery and structural repair in rat contusive injury model. Combination of TMT with NSC TP at 1 week after injury synergistically improved locomotor function. We report here that combining TMT increased the survival of grafted NSCs by >3-fold and >5-fold at 3 and 9 weeks after injury, respectively. The number of surviving NSCs was significantly correlated with the extent of locomotor recovery. NSCs grafted into the injured spinal cord were under cellular stresses induced by reactive nitrogen or oxygen species, which were markedly attenuated by TMT. TMT increased the concentration of insulin-like growth factor-1 (IGF-1) in the CSF. Intrathecal infusion of neutralizing IGF-1 antibodies, but not antibodies against either BDNF or Neurotrophin-3 (NT-3), abolished the enhanced survival of NSC grafts by TMT. The combination of TP and TMT also resulted in tissue sparing, increased myelination, and restoration of serotonergic fiber innervation to the lumbar spinal cord to a larger extent than that induced by either TP or TMT alone. Therefore, we have discovered unanticipated beneficial effects of TMT in modulating the survival of grafted NSCs via IGF-1. Our study identifies a novel neurobiological basis for complementing NSC-based spinal cord repair with activity-based neurorehabilitative approaches.